MANAGING DISRUPTIVE BEHAVIOR OF STUDENTS IN LANGUAGE CLASSROOM - Siti Khasinah (Universitas Islam Negeri Banda Aceh, 2017)
This article describes studentsâ€™ disruptive behaviors in language classroom that may greatly affect language teaching and learning process, especially in ESL or EFL classes. Teachers should know what disruptive behavior is to enable them to deal with problems occurred in their classroom or to take preventive actions to keep their students well-behaved during the class. This can reduce the occurrence of misbehavior of students in their classroom. To prevent disruption in the classroom, teachers should establish behavioral expectations in the first day of the semester and the expectations can be based on students attendance, arrivals and departures, class participation, full English speaking, and other appropriate conducts in the syllabus and discuss them at the outset of the term. The agreement is then assigned as a learning contract or a code of conducts with which bounds the whole class. Consequently, whenever students are misbehaved, teachers and other students will directly know and recognize that the behaviors are out of the code. There are factors reasoning students to behave badly, so teachers as trouble solvers have to find appropriate strategies that are effective in helping students keep the code. Otherwise, the disruptions will escalate quickly and the problems will increase in numbers rapidly and finally, teachers will have to work very hard to avoid teaching failure and â€œlosing faceâ€ when they cannot manage the disruption as listed in the expectation.